PENGARUH PERAN HRD DAN TALENT ACQUISITION TERHADAP KUALITAS REKRUTMEN DAN SELEKSI PADA LKC DOMPET DHUAFA - Sella Susilawati; Giharjo Giharjo; Indri Guslina (Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of Human Resource Development (HRD) Role and Talent Acquisition on Recruitment and Selection Quality at LKC Dompet Dhuafa. In an increasingly competitive environment, organizations are required to acquire qualified human resources through effective recruitment and selection processes. The role of HRD and the implementation of talent acquisition strategies are important factors in supporting the success of these processes. This study employed a quantitative approach using a survey method. The population consisted of all 67 employees of LKC Dompet Dhuafa, and therefore a saturated sampling technique was applied. Data were collected through questionnaires and analyzed using simple and multiple linear regression with IBM SPSS Statistics. The results indicate that the HRD Role has a positive and significant effect on Recruitment and Selection Quality, with a significance value of 0.000 and a coefficient of determination of 62.8%. Talent Acquisition also has a positive and significant effect on Recruitment and Selection Quality, with a significance value of 0.000 and a coefficient of determination of 78.4%. Simultaneously, HRD Role and Talent Acquisition have a positive and significant effect on Recruitment and Selection Quality, with an F-value of 130.057 and a significance level of 0.000. The Adjusted R Square value of 0.796 indicates that both variables explain 79.6% of the variance in Recruitment and Selection Quality. These findings suggest that optimizing the role of HRD and implementing effective talent acquisition strategies can improve the quality of recruitment and selection processes within organizations.